2003
DOI: 10.1128/jb.185.17.5086-5095.2003
|View full text |Cite
|
Sign up to set email alerts
|

Protein Content of Polyhedral Organelles Involved in Coenzyme B 12 -Dependent Degradation of 1,2-Propanediol in Salmonella enterica Serovar Typhimurium LT2

Abstract: Salmonella enterica forms polyhedral organelles during coenzyme B 12 -dependent growth on 1,2-propanediol (1,2-PD). Previously, these organelles were shown to consist of a protein shell partly composed of the PduA protein, the majority of the cell's B 12 -dependent diol dehydratase, and additional unidentified proteins. In this report, the polyhedral organelles involved in B 12 -dependent 1,2-PD degradation by S. enterica were purified by a combination of detergent extraction and differential and density gradi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

26
293
3

Year Published

2005
2005
2018
2018

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 151 publications
(322 citation statements)
references
References 41 publications
26
293
3
Order By: Relevance
“…Although the pathway of 1,2-PD degradation appears quite straightforward, the catabolism of this small molecule is in fact a very elaborate process (Bobik et al, 1999;Havemann et al, 2002;Havemann & Bobik, 2003). Recent studies have shown that a polyhedral body is involved in AdoCbl-dependent 1,2-PD degradation by S. enterica (Bobik et al, 1999;Havemann et al, 2002;Havemann & Bobik, 2003).…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…Although the pathway of 1,2-PD degradation appears quite straightforward, the catabolism of this small molecule is in fact a very elaborate process (Bobik et al, 1999;Havemann et al, 2002;Havemann & Bobik, 2003). Recent studies have shown that a polyhedral body is involved in AdoCbl-dependent 1,2-PD degradation by S. enterica (Bobik et al, 1999;Havemann et al, 2002;Havemann & Bobik, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have shown that a polyhedral body is involved in AdoCbl-dependent 1,2-PD degradation by S. enterica (Bobik et al, 1999;Havemann et al, 2002;Havemann & Bobik, 2003). These polyhedra are 100-150 nm across, (Havemann et al, 2002;Havemann & Bobik, 2003;Leal et al, 2003a).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations